Preparation and characterization of novel UV-curable urethane methacrylate difunctional monomers and their structure-property relationships, 1 - Inan, TY; Ekinci, E; Yildiz, E; Kuyulu, A; Güngör, A (WILEY-V C H VERLAG GMBH, 2001)
Full Paper: Four new UV-curable cross-linking agents namely 2,2-bis(4-beta -ethoxy urethane ethyl methacrylate phenyl)propane (HEPIEM), 2,2-bis(4-beta -ethoxy urethane ethyl methacrylate phenyl)6Fpropane (HEPFAIEM), 2,2- (4-beta -ethoxy urethane ethyl methacrylate-3,5-dibromo phenyl)propane (TBHEPAIEM), and 5-tert-butyl-1,3-bis(4-ethoxy urethane methacrylate phenyl)benzoylbenzene (tBuHEPBIEM), which can be good candidates for UV-curable coating applications, were synthesized by isocyanato ethyl methacrylate (IEM) with four nt diets, The structures of the monomers thus prepared were characterized by FTIR, mass and H-1 NMR spectroscopies. Introduction of new difunctional cross-linking agents affected the mechanical and physical properties of UV-cured films. Addition of 10% cross-linking agents into the formulations caused an increase both in tensile strength and elongation, when compared with widely used di(ethylene glycol)diacrylate (DEGDA) containing films. Elongation values of TBHEPAIEM containing films were exceptions. Gel contents of the UV-cured polymeric films were found to be between 88-98%. Thermogravimetric analysis showed that there were not any noticeable changes in thermal oxidative stability of the films compared with DEGDA containing ones. On the other hand, HEPFAIEM and TBHEPAIEM containing films showed increases in char yields due to the presence of F and Br in their structures. Introduction of the new difunctional monomers lowered the water absorption values of the films somewhat proportional to the methyl group content of the x-linkers.
Keywords: BIS(ARYL CHLORIDE)S; POLYCONDENSATION; Polymer Science